2023
DOI: 10.1101/2023.01.30.525877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salience-based information integration: An overarching function of the “social brain”?

Abstract: Behavior in social contexts is routinely accompanied by neural activity in a brain network comprising the bilateral temporoparietal junction (TPJ), dorsomedial and dorsolateral prefrontal cortex (dmPFC and dlPFC), and precuneus. This network - often referred to as the "social brain network" (SBN) - is thought to have evolved in response to the information processing demands of life in social groups. However, its precise functional contributions to behavior are unclear, since many of its areas are also activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Brain stimulation studies have confirmed that this region is key for norm compliance but not for judgments, as decreasing activity in this region affects the subjects' actions but not their perception of fairness (40,54,74). By contrast, judging norm-violations appears to recruit other regions, such as the temporoparietal junction (TPJ) (75,76) and dorsomedial prefrontal cortex (dmPFC) (77), which are often thought to be involved in the representation of other's thoughts and integration of salient social information (78). Extending our framework to brain imaging experiments would allow us to test directly whether different (or only partially overlapping) sets of brain regions are recruited for actions versus judgments in the same situations, and to capture individual differences in these two sets of neural processes.…”
Section: Discussionmentioning
confidence: 99%
“…Brain stimulation studies have confirmed that this region is key for norm compliance but not for judgments, as decreasing activity in this region affects the subjects' actions but not their perception of fairness (40,54,74). By contrast, judging norm-violations appears to recruit other regions, such as the temporoparietal junction (TPJ) (75,76) and dorsomedial prefrontal cortex (dmPFC) (77), which are often thought to be involved in the representation of other's thoughts and integration of salient social information (78). Extending our framework to brain imaging experiments would allow us to test directly whether different (or only partially overlapping) sets of brain regions are recruited for actions versus judgments in the same situations, and to capture individual differences in these two sets of neural processes.…”
Section: Discussionmentioning
confidence: 99%
“…Determining whether socially relevant cues are processed by domain-specific or domain-general neural circuitry remains an active goal of the social and cognitive neurosciences. While considerable evidence exists for specificity in some domains (e.g., face processing 120-122 122 , emotion recognition [127][128][129] , empathy in different modalities 89 , or even aspects of moral decisionmaking 133 ), other research points to the broad engagement of the mentalizing network across tasks [134][135][136][137][138][139][140] . Given their importance for decision-making, we sought to determine whether perceptions of either need or merit fall within the category of social phenomena processed by dedicated neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…This points to a novel mechanism that is quite different from classic temptation/selfcontrol models of intertemporal choice. Current thinking is that the regions involved in prosocial or temporal decision-making (e.g., the temporoparietal junction or the partially overlapping angular gyrus) provide higher-order cognitive functions that facilitate integration of multisensory input, and that this functionality is particularly useful when building mental representations of complex phenomena, like social context or temporal projection (Jung et al, 2022;Humphreys and Tibon, 2023;Lugrin et al, 2023). Consistent with this conceptualization, Pietrzak et al (2023) found that neural activity in angular gyrus and surrounding areas correlated with decisions in a standard temporal discounting task.…”
Section: Research Agendamentioning
confidence: 99%